CADANGAN COMMISSIONERS ASURANSI DWIGUNA DENGAN FORMULA WOOLHOUSE - Aldila Nur Indah Berliana Ratam; Tumpal Parulian Nababan; Hasriati ' (Jurnal Online Mahasiswa (JOM) Bidang Matematika dan Ilmu Pengetahuan Alam, 2015)
This article discusses the commissioner reserves for endowment insurance, where in determining the annual premium is used single premium and the cash value of the m times annuity payments per year by the Woolhouse’s formula. Moreover, in determining the commissioners reserves is also used commutation functions.